Managing cotton canopy architecture for machine picking cotton via high plant density and plant growth retardants - Sankar Lakshmanan; Selvaraj Somasundaram; Silambiah Shri Rangasami; Pokkharu Anantharaju; Dhashnamurthi Vijayalakshmi; Thiruvengadam Ragavan; Paramasivam Dhamodharan (Journal of Cotton Research)
Abstract Machine picking in cotton is an emerging practice in India, to solve the problems of labour shortages and production costs increasing. Cotton production has been declining in recent years; however, the high density planting system (HDPS) offers a viable method to enhance productivity by increasing plant populations per unit area, optimizing resource utilization, and facilitating machine picking. Cotton is an indeterminate plant that produce excessive vegetative growth in favorable soil fertility and moisture conditions, which posing challenges for efficient machine picking. To address this issue, the application of plant growth retardants (PGRs) is essential for controlling canopy architecture. PGRs reduce internode elongation, promote regulated branching, and increase plant compactness, making cotton plants better suited for machine picking. PGRs application also optimizes photosynthates distribution between vegetative and reproductive growth, resulting in higher yields and improved fibre quality. The integration of HDPS and PGRs applications results in an optimal plant architecture for improving machine picking efficiency. However, the success of this integration is determined by some factors, including cotton variety, environmental conditions, and geographical variations. These approaches not only address yield stagnation and labour shortages but also help to establish more effective and sustainable cotton farming practices, resulting in higher cotton productivity.